2018
DOI: 10.54055/ejtr.v19i.324
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution and relationship of tourist flow in Turkey

Abstract: Tourism is considered as back bone of Turkish economy with its greater share in GDP than many other economic sectors of the country. Present research is sought to analyse the spatial association and distribution of foreign and domestic tourist inflows in 81 provinces of Turkey through exploratory spatial data analysis (ESDA) technique. ESDA is one of very useful Geographic Information System (GIS) based spatial statistics techniques to analyse spatial patterns, identification of hotspots and visualization of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Interpretation Index Tourist volume (Khan, 2018) The number of tourist visits received by the city in a year.…”
Section: Variablementioning
confidence: 99%
“…Interpretation Index Tourist volume (Khan, 2018) The number of tourist visits received by the city in a year.…”
Section: Variablementioning
confidence: 99%
“…In recent years, tourism geography has been developing rapidly, but there are problems such as weak theoretical and methodological research, narrow research scope, and slow improvement in the overall research level (Saarinen et al, 2017). Although the spatial distribution of tourists is an important area where geographers have achieved considerable results (Khan, 2018;Siakwah, 2018), the further development of inbound tourism needs to be studied from multiple perspectives, aspects, and levels. This study not only explored the impact of visa policies on inbound tourism but also revealed the spatiotemporal patterns of inbound tourists and their distribution at a global level, which expands the scope of tourism geography.…”
Section: Theoretical Implicationsmentioning
confidence: 99%